Sunyata Doctrine of Nagarjuna As seen by Master Shen Zhao - Dhammajothi, M. (My University, 2008)
The main issue at the Buddha‟s time was about the soul/self(Ātman=Pali Atta) put forward by many religious teachers, specially the Upanisadic teachings. The Buddha had to show that the belief in an „Ātman‟ is false. So, he emphasized Anatta-no soul doctrine. But the issue Ācārya Nāgārjuna had to face was not about the soul but about the own-nature (Sva-bhāva) of the Sarvāstivādins and other similar substantialist and realist views of Sautrāntikas etc. These schools believed in some unchanging permanent entity that continues. They, while accepting that there is no individual soul (Puggala-nairātmya) agreed that Dharmas or the factors that constitute the person and the world exist in some form. Ācārya Nāgārjuna‟s main task was to show that this, too, is not the Buddha‟s teaching. Therefore he utilized the more wider concept used by the Buddha himself, and adopted the word Suññata (skt. ūnyatā) to show that everything is empty of any permanent, non-changing entity or substance. Thus Ācārya Nāgārjuna emphasized both Pudgalanairātmya (that there is no individual soul)and Dharmanairātmya (that Dharmas are without a soul). To include both these ideas he employed the wider term ūnya or ūnyatā, and presented it as the main teaching of his philosophy. He never claims this to be his view, for he like the Buddha did not have personal views. He was only trying to show the true nature of reality.